UNCOVERING THE DETERMINANTS OF ISLAMIC TOURISM STAKEHOLDERS’ INCOMPREHENSION ABOUT ISLAMIC MUAMALAT - Rafidah Abas; Norhamizan Hamir; Artinah Zainal (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Robust growth of halal industry and its components including Islamic tourism is an aftermath of Islam being the fastest growing religion. Despite the thriving success, stakeholders are facing greater challenges in fulfilling the market demand. Incomprehension about Islamic tourism and Muamalat concept among Islamic tourism stakeholders has adversely affected the Islamic tourism growth. Hence, employing content analysis, the researchers were keen to identify the factors affecting Islamic tourism stakeholders’ poor understanding about Islamic muamalat and how it affects Islamic tourism’s growth. Findings indicated that misunderstanding about Islamic Muamalat among Islamic tourism stakeholders stem from both internal and external factors. Under the Internal factors, demographic profile was found to be the most significant determinant affecting the Islamic tourism operators’ incomprehension about Islamic Muamalat. Besides, lack of understanding about Islamic Muamalat even among Muslim stakeholders was attributed to poor Syariah comprehension. As for the external factors, government policies and business opportunities contributed significantly towards the issue. Consequently, we found that the substandard conception has adverse effect towards the Islamic tourism sector’s growth which reflects its overall credibility and effectiveness. Hence, further explain the potential business owners’ and operators’ reticence to penetrate the market.